Effect of Staphylococcus aureus and Streptococcus uberis on apoptosis of bovine mammary gland neutrophils in vitro - Z. Sladek; D. Rysanek; M. Faldyna (Veterinární Medicína, 2005)
Neutrophils play an important role in the defence of the bovine mammary gland against bacterial infections. In the course of the resolution of mammary gland inflammation, neutrophils undergo programmed cell death - apoptosis. The aim of this study was to confirm whether the co-cultivation of neutrophils of the bovine mammary gland with either Staphylococcus aureus or Streptococcus uberis leads to signs of apoptosis. In the study, 16 mammary glands of four virgin heifers aged 16 to 18 months were examined. Neutrophils were obtained by lavage after an induced influx. After a three-hour incubation of the neutrophils with bacteria in vitro, neutrophil apoptosis was detected by morphological features, by determination of histone-associated DNA fragments (ELISA), and by Annexin -V and propidium iodide positivity (flow cytometry). S. aureus and S. uberis reduced the incidence of karyopycnotic and zeiotic neutrophils (P < 0.01), and insignificantly reduced the concentration of histone -associated DNA fragments (P > 0.05). The incubation of neutrophils with bacteria, however, increased the proportion of Annexin -V-positive cells (P < 0.01) and Annexin -V and propidium iodide-positive cells (P < 0.05). Co-cultivation of neutrophils with either S. aureus or S. uberis led to the induction of phosphatidylserine translocation characteristic of the early stage of apoptosis. The late signs of apoptosis were delayed by co-cultivation of neutrophils with both pathogens. Therefore it is obvious that although the programmed cell death of apoptosis is initiated by these pathogens, the completion of the program is delayed.